Viral pathogens hitchhike with insect sperm for paternal transmission - Mao, Qianzhuo; Wu, Wei; Liao, Zhenfeng; Li, Jiajia; Jia, Dongsheng; Zhang, Xiaofeng; Chen, Qian; Chen, Hongyan; Wei, Jing; Wei, Taiyun (Nature communications, 2019)
Arthropod-borne viruses (arboviruses) can be maternally transmitted by female insects to their offspring, however, it is unknown whether male sperm can directly interact with the arbovirus and mediate its paternal transmission. Here we report that an important rice arbovirus is paternally transmitted by the male leafhoppers by hitchhiking with the sperm. The virus-sperm binding is mediated by the interaction of viral capsid protein and heparan sulfate proteoglycan on the sperm head surfaces. Mating experiments reveal that paternal virus transmission is more efficient than maternal transmission. Such paternal virus transmission scarcely affects the fitness of adult males or their offspring, and plays a pivotal role in maintenance of viral population during seasons unfavorable for rice hosts in the field. Our findings reveal that a preferred mode of vertical arbovirus transmission has been evolved by hitchhiking with insect sperm without disturbing sperm functioning, facilitating the long-term viral epidemic and persistence in nature. Arbovirus vertical transmission is commonly mediated by transovarial passage of female insect vectors. Here, the authors show that Rice gall dwarf virus can be transmitted by male leafhoppers via interactions of the viral capsid and heparan sulfate proteoglycan on the surface of sperm heads.